A novel echocardiographic parameter to identify individuals susceptible to acute mountain sickness. Issue 44 (November 2021) - Ke, Jingbin; Yang, Jie; Liu, Chuan; Qin, Zhexue; Zhang, Jihang; Jin, Jun; Yu, Shiyong; Tan, Hu; Yang, Yuanqi; Zhang, Chen; Li, Jiabei; Yu, Jie; et al.
Abstract: Background: Acute mountain sickness (AMS) may cause life-threatening conditions. This study aimed to screen echocardiographic parameters at sea level (SL) to identify predictors of AMS development. Methods: Overall, 106 healthy men were recruited at SL and ascended to 4100 m within 7 days by bus. Basic characteristics, physiological data, and echocardiographic parameters were collected both at SL and 4100 m above SL. AMS was identified by 2018 Lake Louise Questionnaire Score. Results: After acute high altitude exposure (AHAE), 33 subjects were diagnosed with AMS and exhibited lower lateral mitral valve tissue motion annular displacement (MV TMADlateral ) at SL than AMS-free subjects (13.09 vs. 13.89 mm, p = 0.022). MV TMADlateral at SL was significantly correlated with AMS occurrence (OR = 0.717, 95% CI: 0.534–0.964, p = 0.028). The MV TMADlateral <13.30-mm group showed over 4-fold risk for AMS development versus the MV TMADlateral ≥13.30-mm group. After AHAE, the MV TMADlateral <13.30-mm group had increased HR (64 vs. 74 bpm, p = 0.001) and right-ventricular myocardial performance index (0.54 vs. 0.69, p = 0.009) and decreased left ventricular global longitudinal strain (−21.50 vs. −20.23%, p = 0.002), tricuspid valve E/A ratio (2.11 vs. 1.89, p = 0.019), and MV E-wave deceleration time (169.60 vs. 156.90 ms, p = 0.035). Conclusion: MV TMADlateral at SL was a potential predictor of AMS occurrence and might be associated with differential alterations of ventricular systolic and diastolic functions in subjects with different MV TMADlateral levels at SL after AHAE.